Demonstrating interoperability between unmanned ground systems and command and control systems. (21st May 2021) - Mathiassen, Kim; Schneider, Frank E.; Bounker, Paul; Tiderko, Alexander; Cubber, Geert De; Baksaas, Magnus; Główka, Jakub; Kozik, Rafał; Nussbaumer, Thomas; Röning, Juha; Pellenz, Johannes; Volk, André
This paper describes the research and experiment efforts of the NATO STO group IST-149-RTG capability concept demonstrator for interoperability within unmanned ground systems and C2 and the NAAG team of experts on UGV. The main purpose of the group was to investigate possible standards for controlling UGVs and tests them in a real world scenario. The efforts have been two folded, where the first effort was two NATO groups having an experiment demonstrating interoperability between the UGVs and OCUs available within the group. The Belgium contribution is done in the EU project ICARUS. Both efforts used the Joint Architecture for Unmanned Systems (JAUS) with the interoperability profile (IOP) to successfully enable interoperability between the systems. The trials showed that it is possible to extend the systems quite easily and achieve compliance with parts of the standard in a relatively short time.